The application of combined momentum and blade element theory for aerodynamics performance analysis of rotating blades - M Mohammed, Abdelrazzak Gumaa (2011)
In this thesis, a simulation package for the Six Degrees of Freedom (6DOF ) motion of an underwater vehicle is developed. Mathematical modeling of an underwater vehicle is done and the parameters needed to write such a simulation package are obtained from an existing underwater vehicle available in the literature. Basic equations of motion are developed to simulate the motion of the underwater vehicle and the parameters needed for the hydrodynamic modeling of the vehicle is obtained from the available literature. 6DOF simulation package prepared for the underwater vehicle was developed using the MATLAB environment. S-function hierarchy is developed using the same platform with C++ programming language. With the usage of Sfunctions the problems related to the speed of the platform have been eliminated. The use of S- function hierarchy brought out the opportunity of running the simulation package on other independent platforms and get results for the simulation. Keywords: Underwater Vehicle Simulation, Virtual Reality Modeling Language (VRML ), MATLAB S-function, Simulink, C++, 6DOF.